From Fields to Festivities: Understanding the Cultural Essence of Pongal - Shabir Ahmad Lone; Eugenia Vanina; Kulatunga Mudiyanselage Rohitha Dasanayaka; Alemayehu Erkihun Engida; Rawnaq Ara Parvin; R. Abida Begum; Javad Ahmad Mir; B. Sheela (CV. Radja Publika, 2026)
Pongal is one of the most significant harvest festivals of South India, deeply rooted in agrarian life, cultural traditions, and spiritual gratitude. Celebrated mainly in Tamil Nadu, the festival marks the end of the harvest season and expresses thankfulness to nature, the Sun God, cattle, and the land that sustains life. This study explores the cultural essence of Pongal by tracing its journey from agricultural fields to vibrant festive rituals. The preparation of Pongal rice, community gatherings, traditional music, kolam designs, and cattle worship reflect a close relationship between humans and nature. Beyond its agricultural importance, Pongal serves as a symbol of social unity, shared labor, and collective joy, strengthening bonds within families and communities. The festival also highlights values of simplicity, sustainability, and respect for natural resources. By examining Pongal as both a cultural and social event, the study reveals how this harvest celebration continues to preserve South India’s cultural identity while adapting to modern social contexts.